Dissecting the limited genetic overlap of Parkinson's and Alzheimer's disease. Issue 8 (9th June 2022) - Stolp Andersen, Maren; Tan, Manuela; Holtman, Inge R.; Hardy, John; ,; Pihlstrøm, Lasse
Abstract: Parkinson's disease and Alzheimer's disease show overlapping features both clinically and neuropathologically and elucidating shared mechanisms could have important implications for therapeutic strategies. Evidence for genetic overlap is limited, although enrichment of heritability in genomic regions relevant to microglia has been demonstrated in both disorders. Using summary statistics from genome‐wide association studies, we assessed genetic covariance stratified by cell types and local genetic correlation between Parkinson's and Alzheimer's disease. Significant covariance was observed for neurons only ( p = 0.00046), and local genetic correlation was significant only in the human leukocyte antigen region ( p = 1.0e‐05). Our findings support a minor genetic overlap between these two disorders.